2015
DOI: 10.1179/1743132815y.0000000020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parkinsonism and Parkinson's disease in Qena governorate/Egypt: a cross-sectional community-based survey

Abstract: The overall prevalence of PD disease is high in Nile valley governorates of Upper Egypt compared to other Arabic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 57 publications
1
32
1
Order By: Relevance
“…Parkinson's disease (PD) is the most common cause of Parkinsonism and is expected to affect about nine million patients by the year 2030 [1]. In a previous Egyptian study, the crude prevalence rate of PD was 548/10 5 inhabitants of the studied population [2].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD) is the most common cause of Parkinsonism and is expected to affect about nine million patients by the year 2030 [1]. In a previous Egyptian study, the crude prevalence rate of PD was 548/10 5 inhabitants of the studied population [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are accumulating evidences supporting the role of vitamin D deficiency in the pathogenesis of PD [2]. Long-standing low vitamin D levels may lead to chronic loss of dopaminergic neurons in the central nervous system and, as a consequence, the development of Parkinson's disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PD increases with age; it affects 1% of the population over the age of 60 [1]. Compared to other Arab countries, the prevalence of PD disease is higher in Nile valley governorates of Upper Egypt [2]. Several epidemiologic studies have suggested an inverse relationship between circulating vitamin D levels and the risk of PD.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies having an average quality were included in this review due to the limited number of studies available and due to their valuable contributions to the field. There were eleven cross-sectional studies; four of these estimated the prevalence of Alzheimer's disease, Parkinson's disorder and mild cognitive impairment, and discussed the risks associated with sociodemographic factors; n=944 Palestinian, in addition to n=200 and n=44 Egyptian from two studies, and, n=221 Jordanian (Afgin et al, 2012;Esmayel, Eldarawy, Hassan, Mahmoud, & Mohamed, 2013;Khedr et al, 2015;Almomani, Almomani, Alghadir, Alharethy, & Gabr, 2016). A cross-sectional study in the Netherlands determined the prevalence of dementia and mild cognitive impairment across cultures, based on Arab participants (n=1625), and assessed the validity of the Cross-Cultural Dementia Screening tool .…”
Section: Main Termmentioning
confidence: 99%